2018
DOI: 10.1111/zsc.12291
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and morphological evolution of the so‐called bougainvilliids (Hydrozoa, Hydroidolina)

Abstract: We present phylogenetic analyses (parsimony, maximum likelihood and Bayesian inference) for 69 lineages of anthoathecate hydroids based on 18 morphological characters (12 proposed for the first time) plus mitochondrial (16S and COI) and nuclear (18S and 28S) molecular markers. This study aims to test the monophyly of the present concept of the family Bougainvilliidae, assessing its phylogenetic position within Hydroidolina. Our working hypothesis is used as a context for inferring the evolution of certain morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…All graphs were generated using Python v.3 with ETE Toolkit v.3 [ 34 ], Matplotlib v3.3.1 [ 35 ], and Seaborn v.0.11 [ 36 ] and modified with Inkscape v.0.92 [ 37 ] to improve visualization (e.g., font size and spacing). The tree of Figs 2 and 4 represents a simplified phylogenetic hypothesis obtained by combining phylogenies from previous studies (Scyphozoa [ 38 ], Medusozoa [ 5 ], Hydrozoa [ 39 , 40 ]), taking into account clades with high congruence and support values. Although the different phylogenetic hypotheses were mostly congruent, no single study nor molecular dataset comprised all the terminals discussed here.…”
Section: Methodsmentioning
confidence: 99%
“…All graphs were generated using Python v.3 with ETE Toolkit v.3 [ 34 ], Matplotlib v3.3.1 [ 35 ], and Seaborn v.0.11 [ 36 ] and modified with Inkscape v.0.92 [ 37 ] to improve visualization (e.g., font size and spacing). The tree of Figs 2 and 4 represents a simplified phylogenetic hypothesis obtained by combining phylogenies from previous studies (Scyphozoa [ 38 ], Medusozoa [ 5 ], Hydrozoa [ 39 , 40 ]), taking into account clades with high congruence and support values. Although the different phylogenetic hypotheses were mostly congruent, no single study nor molecular dataset comprised all the terminals discussed here.…”
Section: Methodsmentioning
confidence: 99%
“…Phylogenetic analysis supports the independent origins of a calcified skeleton in Hydrozoa [9,28,29], and the distribution of CaCO 3 polymorphs in their skeletons is considered to have been produced by non-environmental causes [22]. However, Figure 1.…”
Section: Introductionmentioning
confidence: 77%
“…The taxonomy of all species was standardized following the pertinent literature to their area of occurrence (Oliveira et al 2016 and references therein;Ronowicz et al 2019 and references therein;Schuchert 2021). Species were phylogenetically classified according to Maronna et al (2016), Mendoza-Becerril et al (2018) and Schuchert (2021).…”
Section: Data Collectionmentioning
confidence: 99%
“…Along the SSA & A coasts, hydroids-the polyp stage of the cnidarian class Hydrozoa (Cornelius 1992)-are abundant in benthic communities, being usually among the first organisms to settle available space and having the capacity to grow quickly on several natural and artificial substrates (Gili and Hughes 1995;Genzano et al 2009). Recent phylogenetic studies have identified several likely clades corresponding roughly to the suborder or order level in hydrozoan classifications, including Limnomedusae, Leptothecata, Aplanulata, Capitata, and Pseudothecata; the latter three taxa along with a few other groups of "Filifera" are still united under a non-monophyletic "Anthoathecata" (Collins et al 2006;Cartwright et al 2008;Leclère et al 2009;Kayal et al 2015;Maronna et al 2016;Mendoza-Becerril et al 2018).…”
Section: Introductionmentioning
confidence: 99%